ANALYSIS OF SOCIODEMOGRAPHIC FACTORS AND MATERNAL KNOWLEDGE ABOUT BCG IMMUNIZATION - Wigunantiningsih, Ana (Universitas STRADA Indonesia, 2026)
Immunization is a form of government commitment to reducing child mortality. The coverage of UCI in Central Java province in 2019 was 99.98%. Meanwhile, BCG immunization coverage in Karanganyar Regency is lower at 97.2% with pulmonary TB cases in 2019 reaching 245 cases. Mother's knowledge influences mother's behavior in administering BCG immunization. The study used an observational analytical method with a cross sectional approach. The research was conducted at the Karanganyar Regency Regional Health Center in April-May 2021. The instrument used is a questionnaire that has been tested for validity and reliability. Sampling by purposive sampling technique with 35 respondents. Data analysis using logistic regression. The results of the study were obtained that there was a relationship between maternal age and parity with the level of maternal knowledge about BCG immunization with a p value of 0.02 and 0.036, respectively. Socio-demographic factors, namely maternal age, parity, education, employment and family income together have the ability to affect the level of maternal knowledge about BCG immunization by 57.8%, meaning that 42.2% are influenced by other factors outside the study variables.